2020
DOI: 10.1002/smll.202004548
|View full text |Cite
|
Sign up to set email alerts
|

Transformable Dual‐Inhibition System Effectively Suppresses Renal Cancer Metastasis through Blocking Endothelial Cells and Cancer Stem Cells

Abstract: Tumor vasculature and cancer stem cells (CSCs) are two major hazards that accelerate this process. [2,3] Metastatic renal cancer is highly vascularized [4] and the abundant presence of CSCs Tumor vasculature and cancer stem cells (CSCs) accelerate the development of metastatic renal cancer. Dual inhibition of vascular endothelium and CSCs is still a challenge due to their different pathological features. Herein, a transformable dual-inhibition system (TDS) based on a self-assembly peptide is proposed to constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…EVs can also activate VEGF-independent pathways such as those mediated by hepatocyte growth factor (HGF) to enable TKI-induced cell death (Qu et al, 2016). Exosomal miR-19b derived from cancer stem cells could promote angiogenesis (Wang et al, 2020). Exosomal circular RNAs (circRNAs) such as circ-CCAC1 (Xu et al, 2020) and circSHKBP1 (Xie et al, 2020) also involved in angiogenesis.…”
Section: Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs can also activate VEGF-independent pathways such as those mediated by hepatocyte growth factor (HGF) to enable TKI-induced cell death (Qu et al, 2016). Exosomal miR-19b derived from cancer stem cells could promote angiogenesis (Wang et al, 2020). Exosomal circular RNAs (circRNAs) such as circ-CCAC1 (Xu et al, 2020) and circSHKBP1 (Xie et al, 2020) also involved in angiogenesis.…”
Section: Exosomesmentioning
confidence: 99%
“…It was postulated that the dual-inhibition of the ECs and tumor cells/tumor stem cells, or targeting multiple growth factors could significantly inhibit tumorigenesis and angiogenesis. A recent study found that dual-inhibition of the ECs and tumor stem cells significantly inhibits the tumorigenesis and angiogenesis in renal cancer patient-derived xenograft mice (Wang et al, 2020). Besides the resistance of AATs, the benefit of AATs is transient, and efficacy is limited by a fast relapse.…”
Section: Exosomal Circ-ccac1mentioning
confidence: 99%
“…Controllable self-assembly of peptides in living cells via either external or internal stimuli allows for creation of peptide nanostructures with the broad functions ranging from disease diagnosis to treatment. Among the applicable stimuli, enzymes have been considered as one of versatile strategies to regulate the self-assembly of peptides due to their reliable selectivity in the catalysis of chemical reactions. In this context, several enzymes have been utilized in manipulating peptide self-assembly in living cells, including alkaline phosphatase, nitroreductase, caspase-3/7, among others. However, in most cases, expression of the utilized enzymes is only naturally occurring, and there is a lack of intimate association between the expression of enzymes and the self-assembly of peptides. Hence, precisely manipulating the assembly of peptides in specific cells significantly depends on the overexpression of enzymes, thus leading to the limitation of enzymes to the aforementioned categories and particularly for the challenges in the detection of pathological cells at the early stage and interference of their fate.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2017, 60 peptide drugs have been approved by the United States, Europe and other countries [ 28 ]. Recently, peptide self-assembly has become an effective and powerful strategy for the preparation of anti-tumor nanodrugs based on abnormal tumor metabolism and microenvironment, such as overexpression of enzymes [ 29 , 30 ], acidic pH, high GSH level [ 31 ] and specific biomarkers [ 32 , 33 ]. Among them, the study of peptide self-assembly has entered new and exciting frontiers, including the rational design of peptides or their derivatives to enable them to undergo structural changes or morphological transformation in complex biological environments, especially in cells and in vivo [ 34 ].…”
Section: Introductionmentioning
confidence: 99%